2014
DOI: 10.1097/ajp.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Development and Initial Validation of the Pain Assessment Checklist for Seniors With Limited Ability to Communicate-II (PACSLAC-II)

Abstract: Findings indicate that the empirical and theoretically driven revisions to the PACSLAC led to improved ability to differentiate between pain and nonpain states, while retaining its clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 56 publications
2
71
0
Order By: Relevance
“…Nursing home settings.PACSLAC internal consistency ( α  = 0.62–0.92) [336, 337]. PACSLAC-II internal consistency ( α  = 0.74–0.77) [334]. Moderate correlations between PACSLAC scores and global pain intensity ratings ( r  = 0.39–0.54) [337].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nursing home settings.PACSLAC internal consistency ( α  = 0.62–0.92) [336, 337]. PACSLAC-II internal consistency ( α  = 0.74–0.77) [334]. Moderate correlations between PACSLAC scores and global pain intensity ratings ( r  = 0.39–0.54) [337].…”
Section: Introductionmentioning
confidence: 99%
“…Good correlation between PACSLAC scores and VDS ( r  = 0.81) and VAS (0.72–0.86) for unblended rating of acute influenza injection [336]. Both PACSLAC and PACSLAC-II have demonstrated good differentiation between painful and non-painful states in patients ( p  < 0.01) [324, 334]. Good construct validity against NOPPAIN and PAINAD ( r  = 0.66–0.78) [324].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PACSLAC-II items are organized per the six pain assessment domains that have been recommended by the AGS (AGS Panel, 2002). In their study, Chan et al (2014) found that the PACSLAC-II had good psychometric qualities (satisfactory internal consistency and interrater reliability, and good convergent and discriminant validity).…”
Section: Pacslacmentioning
confidence: 97%
“…The PACSLAC-II is a 31-item assessment scale which was recently developed by Chan et al (2014). The PACSLAC-II items were designed to include behaviors that had been shown to discriminate painful and non-painful states while minimizing overlap with behaviors that also occur in non-painful situations such as delirium.…”
Section: Pacslacmentioning
confidence: 99%